Moderasi Beragama dalam Perspektif Pendidikan Agama Islam: Implementasi dalam Pendidikan Multikultural di Indonesia - Wahid, Abdul (Scholars: Jurnal Sosial Humaniora dan Pendidikan, 2024)
Religious moderation is a campaign aimed at public spaces, especially educational institutions, to overcome intolerant attitudes among individuals. Religious moderation from the perspective of Islamic religious education plays an important role in the realization of multicultural education. This research is descriptive-analytical in nature and uses literature review research methods. The research results show that religious moderation plays an important role in the implementation of multicultural education in Indonesia. This success requires cooperation between parents, students, and educational institutions to create an educational environment that is friendly to different religions and helps students become individuals who are tolerant and have good character. Keywords:Religious Moderation, Multicultural Education, and the Implementation of Multicultural Education